The Influence of ICT-Based Think Pair Share Type Cooperative Learning Method (Quizlet) on Student Learning Outcomes on Plant Reproductive Systems - Anggraini, Atika; Rahmawati, Lailatul; Adibowo, Diajeng Lyra (Proceeding International Conference on Education, 2024)
In the current era of information and technology, education must follow technological development so that students can understand better and more effectively. Plant reproductive system material is an important part of the science curriculum. So more innovative and interactive learning methods are needed to increase student understanding. The learning approach that can be adopted is cooperative Think Pair Share type. Cooperative learning methods using Information and Communication Technology based technology such as Quizlet, which is an interavtive online learning platform, can improve the quality of learning. To find out the influence of the Think Pair Share type cooperative learning method on Plant Reproductive Systems material on learning outcomesfor class IX-B students at Mts Nurul Islam, Kediri City. The type of research used is quantitative with experimental design methods. The research designs uses one group pretest posttest. Samples were taken randomly based on discussions with the teacher and the class selected was class IX-B. the data collection technique was carried out by providing pretest and posttest questions as a measuring toolfor this research. The results of the Wilcoxon Matched-Pairs text show that the significance value (p-value) for the Pretest and Posttest scores is 0,000 whre the value is <0,005, which means there is a signifanct difference between the students Pretest and Posttest scores. Student learning outcomes increased significantly after implementing the ICT-based Think Pair Share learning concept using Quizlet. The results show that there is a significant difference between the pre-test and post-test.